2019
DOI: 10.1101/843284
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predictive coding models for pain perception

Abstract: Pain is a complex, multidimensional experience that involves dynamic interactions between sensory-discriminative and affective-emotional processes. Pain experiences have a high degree of variability depending on their context and prior anticipation. Viewing pain perception as a perceptual inference problem, we use a predictive coding paradigm to characterize both evoked and spontaneous pain. We record the local field potentials (LFPs) from the primary somatosensory cortex (S1) and the anterior cingulate cortex… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 87 publications
(138 reference statements)
0
6
0
Order By: Relevance
“…A recent study in rodents has suggested an information flow between S1 gamma and ACC (Anterior Cingulate Cortex) beta activity during spontaneous pain ( Xiao et al, 2019 ). Based on these data, the authors have proposed a predictive coding model including a bottom-up (gamma) and top-down (beta) component ( Song et al, 2019 ). Finally, in humans, a recent EEG study showed that the sensorimotor cortex is more strongly connected to the medial prefrontal cortex at alpha frequencies during tonic pain, suggesting alpha band activity in tonic pain to be associated with bottom-up instead of top-down signaling ( Nickel et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in rodents has suggested an information flow between S1 gamma and ACC (Anterior Cingulate Cortex) beta activity during spontaneous pain ( Xiao et al, 2019 ). Based on these data, the authors have proposed a predictive coding model including a bottom-up (gamma) and top-down (beta) component ( Song et al, 2019 ). Finally, in humans, a recent EEG study showed that the sensorimotor cortex is more strongly connected to the medial prefrontal cortex at alpha frequencies during tonic pain, suggesting alpha band activity in tonic pain to be associated with bottom-up instead of top-down signaling ( Nickel et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Like any other research field, a theory is useful since it helps clarify and motivate thinking associated with observational studies (Levenstein et al, 2023). Similarly, algorithmic inference and high-level computational modeling may reveal insight into computational mechanisms of hierarchical predictive coding in pain studies (Alexander and Brown, 2018;Seymour and Mancini, 2020;Song et al, 2021). However, validation or refinement of this theory still requires further systematic investigations.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report showed that elevated 4 Hz ACC→VTA signaling is associated with anticipatory decision making ("prediction"), whereas error-related feedback integration is associated with increased VTA→ACC signaling ("PE"), which is also predictive of subsequent choice adaptation (Elston et al, 2019). Recently, it has been suggested that the ACC may engage in a top-down prediction in pain perception through alpha/beta oscillations (Song et al, 2021).…”
Section: Representations Of Prediction and Prediction Error In The Ac...mentioning
confidence: 99%
“…Previous research has found increased, mostly at high frequencies, oscillatory activity in either SI, ACC, or both [10,12,13,18,28,38] shortly after intervention with an animal model of pain. Increases in oscillatory activity in one or more cortical areas do not equal changes in connectivity which is why restingstate connectivity is decreased in the minutes or hours following and capsaicin [11] and days or weeks after peripheral nerve injury [11,15].…”
Section: Decreased Short Term Plimentioning
confidence: 92%